MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN MELALUI MEDIA BIG BOOK (Penelitian Tindakan untuk Anak Kelompok B Usia 5-6 Tahun di TK PGRI Panggarangan Lebak Banten) - Panesa Erniawati; Isti Rusdiyani (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2018)
This study aims to improve the ability of early reading through the big book media in the group B children in kindergarten PGRI Panggarangan. This study motivated by the low ability of children in early reading. This research is an action research using Kurt Lewin’s research model which is done in two cycles. in cycle 1 as much as 6 times action and cycle 2 as much as 5 times action, with success criteria 75%. Each cycle at each meeting consists of four stages: planning, action, observation and reflection. Research subjects are 15 children of group B. The research object is the ability of early reading. Data collection techniques in this study are observation, field notes, interview notes and documentation. The research instrument used in the form of observation sheet instrument in the form of check list. Indicators studied is the indicator ability to mention the symbol of the sound of letters, the indicator mentions the same phonemes, and the indicator read the word. Data analysis consists of data reduction, data presentation and conclusion. The results showed that the big book media can improve the ability of early reading. At the pre-action stage the percentage of average achievement of the child just reaches 27,22%. At the implementation of Cycle I percentage is achieved at 50,98%, and the achievement of the early reading ability in cycle II by 75,84%. The increase from pre-action to Cycle I was 23,76% and the increase from Cycle I to Cycle II was 24,86%. Based on the data that has been obtained, it can be concluded that by using the big book media can improve the early reading ability of group B children in kindergarten PGRI Panggarangan.